일본군 '위안부' 지식그래프: 파편화된 디지털 기록의 연결 - 박하람; 김학래; Park, Haram; Kim, Haklae (Journal of Records Management & Archives Society of Korea, 2021)
Records on Japanese "Comfort Women" have been individually managed by private sectors or institutions, and some are provided as digital archives on the Internet. However, records of digital archives differ in the composition and representation of metadata by individual institutions. Meanwhile, there is a lack of a consistent structure to describe the relationships between and among these records, leading to their fragmentation and disconnectedness. This paper proposes a knowledge model for interlinking the digital archival resources and builds a knowledge graph by integrating the records from distributed digital archives. It derives common elements by analyzing metadata from the diverse digital archives and expresses them in standard vocabularies to semantically describe multiple entities and relationships of the digital archival resources. In particular, the study includes the refinement of collected data to search and thread dispersed records and the enrichment of external data to provide significant contextual information of records. An evaluation of the knowledge graph is performed via a query measuring the (dis)connectivity between the distributed records. As a result, the knowledge graph is capable of interlinking and retrieving fragmented records, providing substantial contextual information on the records with external data enrichment, and searching accurately to match the user's intentions through semantic-based queries. 일본군 '위안부'에 대한 기록은 민간 기관에서 개별적으로 관리하고 있다. 일부 기록은 디지털 아카이브로 구축되어 온라인으로 접근할 수 있다. 그러나, 디지털 아카이브의 기록은 기관에 따라 메타데이터의 구성과 표현 방식이 다르다. 한편, 기록 사이의 관계를 정의할 수 있는 체계가 미흡하기 때문에, 현재 구축된 일본군 '위안부' 기록은 서로 연결되지 않고 파편적인 형식으로 남아있다. 본 연구는 일본군 '위안부' 디지털 기록을 연계하기 위한 지식 모델을 제안하고, 분산화된 디지털 아카이브의 기록을 통합하여 일본군 '위안부' 지식그래프를 구축한다. 일본군 '위안부' 디지털 아카이브의 메타데이터를 분석하여 공통 요소를 도출하고, 표준 어휘를 적용하여 디지털 기록의 다양한 개체와 개체 사이의 관계를 의미적으로 표현한다. 특히, 흩어져 있는 기록을 연계하고 검색하기 위해 수집한 데이터의 정제가 이루어지고, 외부데이터를 활용하여 기록의 맥락 정보를 강화하고 있다. 구축된 지식그래프의 검증은 분산된 기록의 탐색 여부를 측정하는 질의를 통해 수행된다. 검증 결과, 지식그래프는 흩어져 있는 기록을 연계하여 검색할 수 있고, 외부데이터로부터의 강화로 기록의 맥락 정보를 풍부하게 제공하며, 의미 기반의 검색을 통해 사용자의 의도에 맞춘 정확한 검색이 가능하다.